Ab initio LSDA and LSDA+U study of pure and Cd-doped cubic lanthanide sesquioxides - Richard, Diego (2013)
The electronic, structural, and hyperfine properties of pure and Cd-doped lanthanide (Ln) sesquioxides with the cubic bixbyite structure (Ln2O3, Ln ranging from La to Lu) have been studied using the full-potential augmented plane wave plus local orbital (APW + lo) method within the local spin density approximation (LSDA) and the Coulomb-corrected LSDA + U. In the case of the pure systems, our calculations show that LSDA + U gives a better representation of the band structure compared to LSDA. The predicted equilibrium structures and the electric field gradient (EFG) tensor at Ln sites were calculated and compared with those obtained by means of hyperfine techniques and with theoretical results obtained in In2O3, Sc2O3, and Lu2O3 reported in the literature. The origin of the EFG at Ln sites and the role played by the 4f electrons on this quantity are discussed. In the case of the Cd-doped systems, the APW + lo method (also within LSDA and LSDA + U) was applied to treat the electronic structure of the doped system. The role of the Ln 4f electrons on the EFG at Cd impurity sites, and other variables like structural distortions induced by the Cd impurity, were investigated in detail and are discussed and compared with available experimental results. An excellent agreement between the experimental and calculated EFGs was found for all Cd-doped systems.